DRAINED LANDS STRUCTURE OF VOLYN REGION AS ECOLOGICAL AND ECONOMIC FACTOR: PRACTICAL ASPECT - Lishchuk, N. M. (Land Management, Cadastre and Land Monitoring, 2013)
Land‐use structure comparative analysis of Volyn region drained lands was done with the help of satellite imagery data and national land cadaster database. Ecological stability and economic productivity of ameliorative complex were estimated. Crop structure and its impact on agricultural production of the region were analyzed.